United Germany : The First Five Years: Performance and Policy Issues - Habermeier, Karl.; Corker, Robert; Feldman, Robert; Van der Willigen, Tessa (Washington, D.C. : International Monetary Fund, 1995)
This papers reviews economic and financial developments in Germany since its reunification nearly five years ago; and analyzes some critical issues that have featured prominently in the policy debate over this period and are likely to continue attracting attention in the years ahead.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet